Internalization of Living Value Education Program (LVEP) as A Based of Developing Conflict Resolution Model - Wasis Suprapto; Bunyamin Maftuh; Helius Sjamsuddin; Elly Malihah (JETL (Journal of Education, Teaching and Learning), 2021)
Violence become a serious problem in this country. All parties including students have been involved in this swirl of problems. The phenomenon of violence in the educational environment can be minimized by internalizing the Living Value Education Program (LVEP) in learning activities. LVEP internalization is carried out as a reference basis in developing resolution models in social studies learning. This article focuses on examining (1) the process of internalizing values in social studies learning, (2) the importance of including LVEP in the learning process, and (3) making LVEP the basis for developing a conflict resolution model. Articles are reviewed using literature study. The results showed that (1) the process of internalizing values in social studies learning was carried out in order to prepare students to become good citizens. (2) LVEP contains universal values such as peace, respect, love, cooperation, happiness, honesty, humility, responsibility, simplicity, tolerance, freedom and unity which can be used as a reference in classroom learning activities. (3) LVEP can be used as a reference in developing a conflict resolution model because it contains values of peace-loving, tolerance, and upholds the value of national unity and integrity